Iron(III) metallomesogen of [N2O2] donor Schiff base ligand containing 4-substituted alkoxy chains. Issue 11 (1st September 2016) - Pramanik, Harun A. R.; Chanda, Soumitra; Bhattacharjee, Chira R.; Paul, Pradip C.; Mondal, Paritosh; Prasad, S. Krishna; Shankar Rao, D. S.
ABSTRACT: Two new square pyramidal iron(III)-complexes of 'salen'-type Schiff base ligands containing 4-substituted long alkoxy arms on the aromatic rings, [Fe(4-C16 H33 O)2 salcn)]Cl and [Fe(4-C16 H33 O)2 salophen)]Cl {salcn = N, Nʹ-cyclohexanebis(salicylideneiminato) and salophen = N, Nʹ-phenylenebis(salicylideneiminato)}, have been successfully synthesised, and their mesomorphic property investigated. The ligands and complexes were characterised by elemental analyses, UV–Vis, FT-IR, ESI–MS, 1 H and 13 C NMR (for ligands only). The phase behaviour of the iron(III) complexes were ascertained by differential scanning calorimetry, polarising optical microscopy and variable temperature PXRD study. Ligands are non-mesomorphic, however, mesomorphism got induced upon complexation with the iron(III) centre. X-ray diffraction study revealed a layer-like arrangement of the five coordinated mesomorphic iron(III) complexes. The mesophase is stable over a wide range of temperature. The density functional theory calculations were carried out using Gaussian 09 program at B3LYP level using unrestricted 6–31G (d, p) basis set to obtain the optimised geometry of the iron(III) complexes. Graphical Abstract: